The road to a polio-free Uganda; contribution of the Expanded Program on Immunization Laboratory (EPI-LAB) at Uganda Virus Research Institute - Nanteza, Mary B.; Tushabe, Phionah; Bukenya, Henry; Namuwulya, Prossy; Kabaliisa, Theopista; Birungi, Molly; Tibanagwa, Mayi; Ampeire, Immaculate; Kakooza, Proscovia; Katushabe, Edson; Bwogi, Josephine; Bakamutumaho, Barnabas; et al. (African Health Sciences, 2023)
Background: The control of poliomyelitis in Uganda dates back as far as 1950 and acute flaccid paralysis (AFP) surveillance has since been used as a criterion for identifying wild polioviruses. Poliovirus isolation was initially pursued through collaborative research however, in 1993, the Expanded Program on Immunization Laboratory (EPI-LAB) was established as a member of the Global Poliovirus Laboratory Network (GPLN) and spearheaded this activity at Uganda Virus Research Institute. Objectives: The aim of this report is to document the progress and impact of the EPI-LAB on poliovirus eradication in Uganda. Methods: Poliovirus detection and identification were achieved fundamentally through tissue culture and intra-typic differentiation of the poliovirus based on the real-time reverse transcriptase polymerase chain reaction (rRT PCR). The data obtained was entered into the national AFP database and analysed using EpiInfoTM statistical software. Results: Quantitative and qualitative detection of wild and Sabin polioviruses corresponded with the polio campaigns. The WHO target indicators for AFP surveillance were achieved essentially throughout the study period. Conclusion: Virological tracking coupled with attaining standard AFP surveillance indicators has been pivotal in achieving and maintaining the national wild polio-free status. Laboratory surveillance remains key in informing the certification process of polio eradication.